P02-08 Using ToxTracker and DNA Repair-Deficient Cell Lines to Determine the Genotoxic Mode of Action of N-Nitrosamines - P. van Rossum; A. Gernaat; M. Hoogenboom-Geijer; D. Roberts; I. Brandsma; N. Moelijker; G. Hendriks (Toxicology Letters, 2024)

Risks associated with global warming of 1.5 to 4 °C above pre-industrial levels in human and natural systems in six countries - R. Warren; J. Price; N. Forstenhäusler; O. Andrews; S. Brown; K. Ebi; D. Gernaat; P. Goodwin; D. Guan; Y. He; D. Manful; Z. Yin; et al. (Climatic Change, 2024)
The Topical Collection “Accrual of Climate Change Risk in Six Vulnerable Countries” provides a harmonised assessment of risks to human and natural systems due to global warming of 1.5–4 °C in six countries (China, Brazil, Egypt, Ethiopia, Ghana, and India) using a consistent set of climate change and socioeconomic scenarios. It compares risks in 2100 if warming has reached 3 °C, broadly corresponding to current global greenhouse gas emission reduction policies, including countries’ National Determined Contributions, rather than the Paris Agreement goal of limiting warming to ‘well below’ 2 °C and ‘pursuing efforts’ to limit to 1.5 °C. Global population is assumed either constant at year 2000 levels or to increase to 9.2 billion by 2100. In either case, greater warming is projected to lead, in all six countries, to greater exposure of land and people to drought and fluvial flood hazard, greater declines in biodiversity, and greater reductions in the yield of maize and wheat. Limiting global warming to 1.5 °C, compared with ~ 3 °C, is projected to deliver large benefits for all six countries, including reduced economic damages due to fluvial flooding. The greatest projected benefits are the avoidance of a large increase in exposure of agricultural land to severe drought, which is 61%, 43%, 18%, and 21% lower in Ethiopia, China, Ghana, and India at 1.5 °C than at 3 °C, whilst avoided increases in human exposure to severe drought are 20–80% lower at 1.5 °C than 3 °C across the six countries. Climate refugia for plants are largely preserved at 1.5 °C warming in Ghana, China, and Ethiopia, but refugia shrink in areal extent by a factor of 2, 3, 3, 4, and 10 in Ghana, China, India, Ethiopia, and Brazil, respectively, if warming reaches 3 °C. Economic damages associated with sea-level rise are projected to increase in coastal nations, but more slowly if warming were limited to 1.5 °C. Actual benefits on the ground will also depend on national and local contexts and the extent of future investment in adaptation.

Global and regional aggregate damages associated with global warming of 1.5 to 4 °C above pre-industrial levels - R. Warren; C. Hope; D. E. H. J. Gernaat; D. P. Van Vuuren; K. Jenkins (Climatic Change, 2021)
We quantify global and regional aggregate damages from global warming of 1.5 to 4 ° C above pre-industrial levels using a well-established integrated assessment model, PAGE09. We find mean global aggregate damages in 2100 of 0.29% of GDP if global warming is limited to about 1.5 °C (90% confidence interval 0.09–0.60%) and 0.40% for 2 °C (range 0.12–0.91%). These are, respectively, 92% and 89% lower than mean losses of 3.67% of GDP (range 0.64–10.77%) associated with global warming of 4 °C. The net present value of global aggregate damages for the 2008–2200 period is estimated at $48.7 trillion for ~ 1.5 °C global warming (range $13–108 trillion) and $60.7 trillion for 2 °C (range $15–140 trillion). These are, respectively, 92% and 90% lower than the mean NPV of $591.7 trillion of GDP for 4 °C warming (range $70–1920 trillion). This leads to a mean social cost of CO 2 emitted in 2020 of ~ $150 for 4 °C warming as compared to $30 at ~ 1.5 °C warming. The benefits of limiting warming to 1.5 ° C rather than 2 ° C might be underestimated since PAGE09 is not recalibrated to reflect the recent understanding of the full range of risks at 1.5 ° C warming.